ChemInform Abstract: 1, 1′‐Bis(diphenylphosphino)ferrocene in Functional Molecular Materials. Issue 5 (13th February 2013) - Young, David J.; Chien, Sheau Wei; Hor, T. S. Andy
Abstract Review: 59 refs.